Peran Teman Sebaya Terhadap Perilaku Bullying di Sekolah - Puspita, Mefrie; Octavia, Dian; Yan, Loriza Sativa (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Bullying is still a major issue in today's society. Bullying is one of them, and it can happen in a school environment. Children may feel hopeless, have low self-esteem, have anxiety, have sleep problems, have a desire to harm themselves, and have a reluctance to go to school. The principal, teachers, students, and classmates can all be bullies in the classroom. In SDN 116/IV Jambi City in 2019, this study attempts to determine the association between peer roles and bullying behavior. This is a quantitative research project with a cross-sectional design. 214 students were chosen as research samples using a basic random sampling procedure. The findings revealed minor bullying behavior as well as the influence of negative peers. There is a strong link between peer bullying and bullying behavior. Bullying may be prevented by integrating all elements of a child's life and implementing anti-bullying programs that include monitoring and sanctioning perpetrators.